Plataforma para coleta e visualização de dados agrícolas georreferenciados em ambiente web e mobile - Pergher, Alexandro Patrik (2015)
Information Systems can improve workflow, speed and security of processes. In the academic area, although new discoveries are always researchers purposes, some processes are established and are not submitted to severe changes throughout time. The data collection follows a given standard, where the collection points and variables are defined then the procedure is executed, recording variable values on each sample. Tools which automate this process are not popular. In cases concerning data where the occurrence place is crucial, the available systems are scarcer. This information is characterized as georeferenced structures, with known coordinates, in some reference system. So, new technologies of information and communication applied in this study resulted in a software that share and present accordingly the field research data, in order to help the Topography and Geoprocessing Lab (GeoLab) researchers of Western Paraná State University, campus, Cascavel, in their agricultural activities. The research of Topography and Geoprocessing Lab has improved the agriculture on Western Paraná. In order to contribute for new progresses in this field, that has Brazilian GDP relevance, some interviews with researchers of GeoLab was done. Thus, aiming at contributing with more relevant breakthroughs for Brazilian GDP and for this area, interviews were conducted with researchers at the lab, examining documents and spreadsheets used for data collection, and a flexible data model was created to meet the numerical data, alphanumeric, temporal, spatial and logical storage. Thus, during the solution development, Java 8 platform, PostgreSQL 9.4 relational database, PostGIS 2.1 extension, and some UML artifacts for documentation were used as well as some UML artifacts for documentation.